Structure‐property relations in crack‐resistant alkaline‐earth aluminoborosilicate glasses studied by solid state NMR. Issue 5 (24th January 2021) - Logrado, Millena; Eckert, Hellmut; Murata, Tetsuya; Nakane, Shingo; Yamazaki, Hiroki
Abstract: The effect of the average ionic potential ξ = Ze / r of the network modifier cations on crack initiation resistance ( CR ) and Young's modulus E has been measured for a series of alkaline‐earth aluminoborosilicate glasses with the compositions 60SiO2 –10Al2 O3 –10B2 O3 –(20− x )M(2) O– x M'O (0 ≤ x ≤ 20; M, M' = Mg, Ca, Sr, Ba, Na). Systematic trends indicating an increase of CR with increasing ionic potential, ξ, have been correlated with structural properties deduced from the NMR interaction parameters in 29 Si, 27 Al, 23 Na, and 11 B solid state NMR. 27 Al NMR spectra indicate that the aluminum atoms in these glasses are essentially all four‐coordinated, however, the average quadrupolar coupling constant Q > extracted from lineshape analysis increases linearly with increasing average ion potential computed from the cation composition. A similar linear correlation is observed for the average 29 Si chemical shift, whereas the fraction of four‐coordinate boron decreases linearly with increasing ξ . Altogether the results indicate that in pure alkaline‐earth boroaluminosilicate glasses the crack resistance/ E ‐modulus trade‐off can be tailored by the alkaline‐earth oxide inventory. In contrast, the situation looks more complicated in glasses containing both Na2 O and the alkaline‐earth oxides MgO, CaO, SrO, and BaO. For 60SiO2 –10Al2 O3 –10B2 O3 –10MgO–10Na2 O glass, the NMR parameters, interpreted in the context of their correlations with ionic potentials, are consistent with a partial network former role of the MgO component, enhancing crack resistance. Altogether the presence of MgO in aluminoborosilicate glasses helps overcome the trade‐off issue between high crack resistance and high elasticity modulus present in borosilicate glasses, thereby offering additional opportunities for the design of glasses that are both very rigid and very crack resistant.